2019
DOI: 10.1016/j.contraception.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Patient recommendations for PrEP information dissemination at family planning clinics in Atlanta, Georgia

Abstract: Objective: Family planning (FP) clinics are an ideal setting to disseminate information about pre-exposure prophylaxis (PrEP), but little is known about women's preferences for learning about PrEP in this setting. Study design:We surveyed 500 women seeking care at 4 FP clinics in Atlanta. Before their provider visit, participants completed an HIV-risk screener. After, we asked participants about the HIV prevention counseling they received and how clinics could share information about PrEP. We performed descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Clinics in the “Incompatible Setting” group may consider this referral adaption, so that women who could benefit from PrEP are at a minimum educated and made aware of the availability of PrEP services in their community. Universal education pertaining to PrEP is especially important given consistently low knowledge and awareness about PrEP reported among women in the South [ 5 , 7 ]. Other potential adaptations to PrEP, that could help overcome barriers, include pharmacy-based PrEP services (which could be useful for clinics that have a pharmacy on-site) [ 52 ], telemedicine [ 53 ], and at-home PrEP services [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinics in the “Incompatible Setting” group may consider this referral adaption, so that women who could benefit from PrEP are at a minimum educated and made aware of the availability of PrEP services in their community. Universal education pertaining to PrEP is especially important given consistently low knowledge and awareness about PrEP reported among women in the South [ 5 , 7 ]. Other potential adaptations to PrEP, that could help overcome barriers, include pharmacy-based PrEP services (which could be useful for clinics that have a pharmacy on-site) [ 52 ], telemedicine [ 53 ], and at-home PrEP services [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-silencing is one factor that influences traditional gender roles; it restricts self-expression undermining a woman’s feelings, thoughts, and actions in maintaining an intimate relationship (Maji & Dixit, 2019). Similarly, being subordinate to others is indicative of women’s obedience and respect for the hierarchical family structure, particularly toward men and elders (Sanchez et al, 2019). Control of sexual interactions between men and women occurs under power inequalities that force women to be passive sexually which can contribute to a reluctance to protect oneself against HIV, since it requires a degree of sexual autonomy (El-Bassel et al, 1998; Fasula et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PrEP-related research indicates knowledge as an important factor that influences PrEP interest, willingness, and uptake (Collier et al, 2017;Garfinkel et al, 2017;Rubtsova et al, 2013). Qualitative and quantitative studies on PrEP knowledge and acceptability among women in the U.S. have demonstrated wide approval of PrEP use as a female controlled prevention method (Auerbach et al, 2015;Bond & Gunn, 2016;Ravasi et al, 2016;Rubtsova et al, 2013;Sales et al, 2019). A recent study on PrEP interest found that social networks can influence PrEP use among women of color experiencing IPV (Willie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Data from family planning clinics in Georgia suggest that women want waiting-room materials on PrEP, such as brochures and posters, and that 39% wanted doctors to initiate discussions on PrEP. 16 Woman-centered PrEP materials continue to be developed and a list of patient and provider resources can be found at hiveonline.org. It was also suggested that one clinician be identified as the ''PrEP Champion,'' to take the lead in addressing systems issues.…”
Section: Discussionmentioning
confidence: 99%